Multi-response and multi-criteria optimization of acid hydrolyzate detoxification of cocoa pod husks: Effect on the content of phenolic compounds and fermentable sugars - Ouattara Leygnima Yaya; Kouassi Esaïe Kouadio Appiah; Soro Doudjo; Amadou Kiari Mahamane Nassirou; Fanou Guy Didier; Yao Kouassi Benjamin; Allali Patrick Drogui; Dayal Rajeshwar Tyagi (Heliyon, 2023)
Dilute acid hydrolysis is the most common and effective method for converting lignocellulosic substrates into fermentable sugars. However, this hydrolysis partially degrades the lignin into phenolic compounds (PC), inhibiting the fermentation medium by retaining it in the hydrolyzate. Response surface methodology is a modeling and optimization technique used to examine the effect of multiple factors on a given response. In this study, shows the removal of PC from cocoa pod husks hydrolyzate, while preserving a considerable level of reducing sugar (RS). An Alkalinization from pH 11 with NaOH, then readjustment of pH to 6 with H2SO4 were first carried out, while eliminating 89.39% of PC and 13.41% of sugars. Then, an optimization of the activated carbon detoxification of the hydrolyzate was carried out by considering the contact time factors (X1), carbon to hydrolyzate ratio (X2) and the agitation speed (X3) in a Box-Behnken plan. The optimal conditions were 60 min of contact, a carbon to hydrolyzate ratio of 1.984% (w/v), and a stirring speed of 180 revolutions per minute (rpm). 0.153 mg/mL of PC and 6.585 mg/mL of RS remained in the hydrolyzate, corresponding to 95.18% of PC and 28.88% of RS lost.